Longitudinal Evaluation of Serum MOG-IgG and AQP4-IgG Antibodies in NMOSD by a Semiquantitative Ratiometric Method - Bollo, Luca; Iaffaldano, Pietro; Ruggieri, Maddalena; Palazzo, Claudia; Mastrapasqua, Mariangela; Manni, Alessia; Paolicelli, Damiano; Frigeri, Antonio; Trojano, Maria (Frontiers in Neurology, 2021)
Background and purpose: Immunoadsorption (IA) is an antibody-depleting therapy used to treat Neuromyelitis optica spectrum disorder (NMOSD) associated to anti-aquaporin4 (AQP4-IgG) and anti-myelin oligodendrocyte glycoprotein (MOG-IgG) serum autoantibodies. Our aim was to evaluate longitudinal changes of serum MOG-IgG and AQP4–IgG antibody titer and to correlate it with the clinical status. Methods: Autoantibody titer and clinical features of two MOG-IgG+/AQP4-IgG- and two AQP4-IgG+/ MOG-IgG- patients with NMOSD were collected at baseline (T0), after 6 IA courses (T1), and then two weeks (T2) and 6 months after treatment (T3). A fluorescent ratiometric assay was used for a quantitative detection of MOG and AQP4 antibodies, based on HEK-293 cells transfected with the full-length hMOG fused to GFP or h-AQP4-M23 isoform fused to m-cherry respectively. We defined the antibody titer as MOG quantitative ratio (MOGqr) and AQP4 quantitative ratio (AQP4qr). Results: In Case 1 the MOGqr dropped from 0.98 at T0 to 0.14 at T3 and in Case 2 decreased from 0.96 at T0 to undetectable at T3. In Case3 the AQP4qr remained high: 0.90 at T0 and 0.92 at T3. In Case 4 the AQP4qr decreased from 0.50 at T0 to undetectable at T3. Complete recovery was found in Case 1,2 and 4. Conclusions: Semiquantitative ratiometric method accurately detects even slight variation of MOG-IgG and AQP4-IgG titer, suggesting it may be useful to monitor the antibody titer during the disease course and maintenance immunotherapy.